Voment Electrical (Volt Measuring Tools of Electrical Materials): Voice-activated DC Voltage Meter for the Blind: Physics Education - Al Hanani, Moh Lutfi Salim; Miyaqi, Iqlides Ahmad; Putra, Ricky Armando; Winarti (Impulse: Journal of Research and Innovation in Physics Education, 2025)
Science learning involves studying natural phenomena in the universe, such as dynamic electricity. Dynamic electricity is a topic that frequently requires measurements during instruction. This presents a challenge for visually impaired students, because they are unable to read the measurement results displayed visually, therefore, innovation in measuring tools with audio output is necessary. Voment Electrical (Electric Voltage Measuring Instrument) is a DC voltage measuring instrument with audio output, which is a development of a digital voltmeter. This tool uses an Arduino Nano as a microcontroller and voltage sensor. The voltage value measured on this tool is output in the form of sound. Therefore, this tool can be an alternative measuring tool in dynamic electricity learning that can overcome the limitations of blind children in making measurements. The objectives of this study are 1) Designing Voment Electrical: a sound-output DC voltage measuring instrument for impaired children on dynamic electricity material, and 2) Testing Product Feasibility. This research is a development research with a 4D research method. Data was collected through evaluation sheets from media and subject-matter experts. Data analysis from the assessment sheets of media experts and material experts is used to determine the quality of the device developed. Based on the research results, the device's quality was rated "Excellent" by both media and subject-matter experts, with average scores of 3.54 and 3.42. Therefore, this voltage measuring tools of electrical materials for visually impaired students is appropriate for teaching dynamic electricity in physics learning.